Calculation of the Coulomb barrier and the level density parameter at the fission saddle point in spallation nuclear reactions. (15th October 2018) - Tumbarell, O; Guzmán, F; Velasco, F G; Castillo, J L Bernal; Rodriguez, O; Samana, A; Andrade-II, E; Deppman, A
Abstract: This work studies the compound nucleus' de-excitation during spallation nuclear reactions, with focus on the behavior of the Coulomb barrier for emission of charged particles and the level density parameter at the fission saddle point, establishing for the first time a relationship between these magnitudes and the level density. This relationship manifests itself through two differential equations explicitly dependent on the excitation energy and the level density parameter of the nucleus after the emission of light particles. These equations were implemented into the CRISP code and used to simulate proton induced spallation reactions on 208 Pb and 238 U, respectively, comparing the results with data coming from GSI experiments as well as from other codes and obtaining satisfactory results that confirm the reliability of the new models.